Prevalence of anti-HBV antibodies in multi-transfused patients with thalassemia at Thi-Qar province - Al-Badry, Bushra Jabbar (University of Thi-Qar Journal of Science, 2014)
AbstractThe present study was carried out from September 2012 to May 2013 to detect the epidemiology of Hepatitis B virus infections among the Thalassemia patients, represent patients referred to the center of thalassemic /AL-Haboby Hospital, central blood bank, at Thi-Qar province. The ELISA-III technique was implemented. This study was conducted on 457 individuals from thalassemic patients: 252 males and 205 females . Seropositive results of HBV by ELISA III technique was found in 5(1.09%), the infections were distributed as the following: males 4(1.58%) were higher than females 1(0.48%), with significant differences (P≤0.01). The statistical analysis showed significant differences in urban than rural parts of the province (p<0.01). The highest infection rates recorded was 2.38% ,1.11% and 1.02% at age groups 11-15 , 16-20 and > 21 years) respectively.Our results have revealed that hepatitis B vaccine is highly immunogenic for children with thalassemia and particularly well tolerated. According to our findings most thalassemic patients (98.91%) were immune to HBV and 1.09 % of them were not immune to HBV.